Political Knowledge: Assessing the Stability of Gender Gaps Cross-Nationally. (19th April 2019) - Fortin-Rittberger, Jessica
Abstract: This article investigates gender gaps in political knowledge by exploiting a pooled dataset containing the four modules of the Comparative Study of Electoral Systems, thereby allowing the comparison of seven different measurements of political knowledge, the most comprehensive comparison to date. The paper's findings are threefold. First, the two conventional types of political knowledge—factual or placement knowledge—belong to different latent constructs and are not interchangeable. Second, most factual knowledge scales produce important variations in the size of gender gaps across and within countries over time. Third, "don't know" as an incorrect response generally leads to broader gender gaps, given men's higher propensity to guess.